Large stroke quasi-zero stiffness vibration isolator using three-link mechanism - Yan, Ge; Zou, Hong-Xiang; Wang, Sen; Zhao, Lin-Chuan; Gao, Qiu-Hua; Tan, Ting; Zhang, Wen-Ming (Journal of sound and vibration, 2020)
Quasi-zero stiffness (QZS) is beneficial for low-frequency vibration isolation. However, most isolators based on QZS have a small working stroke and a limited load capacity, which hinders applications in many environments. Here, a large stroke QZS vibration isolator using three-link mechanisms (TLMs) is proposed. We design a symmetric polygon structure consisting of two three-link structures which exhibits a linear negative stiffness with large displacement. Then, the quasi-zero stiffness with large stroke could be realized by parallel connection of the symmetric polygon structure and linear springs. In addition, the load capacity of the proposed QZS system is extended by 1.5–2 times compared with a single polygon structure and can be flexibly adjusted. The design philosophy and operation principle of QZS isolator using TLMs are described in detail. The dynamic model is established based on the Lagrange equation. Numerical and experimental results demonstrate that the large stroke QZS vibration isolator has a lower resonant frequency and outperforms the linear counterpart especially at low frequencies. Moreover, the proposed isolator is less sensitive to vibration amplitude than the traditional QZS isolator. This novel design may provide a feasible method for large amplitude low frequency vibration control and isolation.